Lifetime Degradation by Oxygen Precipitation Combined with Metal Contamination in Czochralski Silicon for Solar Cells. (1st January 2019) - Onishi, Kohei; Kinoshita, Kosuke; Kojima, Takuto; Ohshita, Yoshio; Ogura, Atsushi
Abstract : Metal impurities which cause degradation of the carrier lifetime are incorporated into the device from the feedstock, during the slicing process or the thermal process. Oxygen precipitates in Czochralski silicon (Cz-Si) have been used as internal gettering sources for metals in the integrated circuit device fabrication. In this study, lifetime degradation caused by oxygen precipitates combined with metal contamination in Cz-Si for solar cells was evaluated for the samples with different interstitial oxygen concentrations using photoluminescence imaging and infrared light scattering tomography. Samples with and without oxygen precipitation thermal treatment were intentionally contaminated with FeCl3  solution, and then phosphorus diffusion gettering (PDG) was carried out. It was confirmed that PDG is effective for the samples with low oxygen concentration, however the lifetime was not recovered for the samples with high oxygen concentration when subjected to intentional metal contamination even after PDG. The oxygen precipitation promotion process made it more difficult to recover from the metallic contamination. We have shown that the high density and large size oxygen precipitates have negative effect on the lifetime in combination with metal impurities.